Cardiovascular, autonomic, and plasma catecholamine responses in unilateral and bilateral carotid artery stenosis. Issue 4 (1st October 1999) - Akinola, Adeola; Mathias, Christopher J; Mansfield, Averil; Thomas, David; Wolfe, John; Nicolaides, A N; Tegos, Thomas
Abstract : OBJECTIVE: To determine impairment of baroreceptor afferent activity, which may affect cardiovascular autonomic function in patients with unilateral and bilateral carotid artery stenosis. Comparison was made with normal subjects and hypertensive patients. METHODS: A series of cardiovascular autonomic function tests along with plasma noradrenaline (norepinephrine) measurements were performed in 46 patients with carotid artery stenosis (CAS); 23 had unilateral and 23 had bilateral stenosis. Comparison was made with 21 hypertensive patients (with a similar degree of raised blood pressure), and 27 normal subjects. RESULTS: Over a third of patients with unilateral and bilateral CAS had postural hypotension. Heart rate did not rise appropriately in CAS despite the postural fall in blood pressure. Pressor responses in CAS were preserved. Heart rate responses to respiratory stimuli were attenuated. Plasma noradrenaline concentrations rose normally during head up tilt. CONCLUSION: A substantial proportion with CAS had postural hypotension and attenuated heart rate responses. This was not due to sympathetic vasoconstrictor or cardiac parasympathetic failure, thus suggesting impaired afferent baroreceptor activity, probably secondary to involvement of the carotid sinus. Cardiovascular autonomic testing and assessment of postural hypotension and factors enhancing it may be of clinical relevance in such patients, especially as the symptoms of postural hypotension overlap with those due to thromboembolism.